2013
DOI: 10.1016/j.adolescence.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparing reports of peer rejection: Associations with rejection sensitivity, victimization, aggression, and friendship

Abstract: Perceiving that one is rejected is an important correlate of emotional maladjustment. Yet, self‐perceptions can substantially differ from classmate‐reports of who is rejected. In this study, discrepancies between self‐ and classmate‐reports of rejection were identified in 359 Australian adolescents (age 10–12 years). As expected, adolescents who overestimated rejection reported more rejection sensitivity and felt more victimized by their peers, but were not seen by peers as more victimized. Adolescents who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 78 publications
3
26
1
1
Order By: Relevance
“…Findings indicated that during this developmental stage, perceptions of the self and of one's social interaction partners are closely intertwined. The more adolescents liked (or disliked) their peers, the more they believed they were liked (or disliked), consistent with previous research demonstrating metaperceptions as relatively independent of others' evaluations (Kenny and DePaulo 1993; Sung et al 2010; Zimmer-Gembeck et al 2013). Adolescents may rely on their own views to determine what others may be thinking, perhaps following an “if I like you, then you must like me” logic.…”
Section: Discussionsupporting
confidence: 87%
“…Findings indicated that during this developmental stage, perceptions of the self and of one's social interaction partners are closely intertwined. The more adolescents liked (or disliked) their peers, the more they believed they were liked (or disliked), consistent with previous research demonstrating metaperceptions as relatively independent of others' evaluations (Kenny and DePaulo 1993; Sung et al 2010; Zimmer-Gembeck et al 2013). Adolescents may rely on their own views to determine what others may be thinking, perhaps following an “if I like you, then you must like me” logic.…”
Section: Discussionsupporting
confidence: 87%
“…Namely, during adolescence, while relationships with close adults remain important, peers take on a central role in adolescents’ lives and further socio-emotional development and adjustment (e.g., Blakemore and Mills 2014). In fact, the role of peer rejection has been identified as having an important impact on the development of both externalizing (Asher and McDonald 2009) and prosocial behaviors (Zimmer-Gembeck et al 2013). While we controlled for the influence of peers prior to the teacher change, students may have, very plausibly, developed new peer relationships in the time between the teacher change, teacher–student relationship assessment and the 2–5 years follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, the factorial structure of the scale was checked, and it was decided to use a stricter items' selection to keep only the items that tackled bullying behavior. Future studies could test the associations of subtypes of aggression with social status and the effects of group features, and consider different reporting sources (peer, self, teachers), since previous studies have shown differences regarding who reports on bullying (Berger & Rodkin, 2009;Zimmer-Gembeck et al, 2013). Another limitation is the cross-sectional nature of the data that does not allow for testing causal associations and developmental trends.…”
Section: Discussionmentioning
confidence: 99%